(untitled) (Research, Society and Development, 2020)
According to the Ministry of Health, teenage pregnancy is assessed as a public health problem, considered to be a high risk factor and related to biological and social complications in maternal and fetal conditions. Self-care provides the necessary recognition that adolescents need to be actively involved in the pregnancy process. This article aims to identify the self-care practices of pregnant adolescents. This is an integrative literature review. In the results, most adolescents reported having a steady partner (73.3%), did not show body dissatisfaction (82.1%), lived in peripheral neighborhoods, with a large number of people with low income and low education. Greater self-care was evidenced in relation to the consumption of toxic substances, such as alcohol and drugs, hygiene, rest and food. Care, such as physical exercise, sunscreen and breast care, were not considered priorities by pregnant women. From the study carried out, it was possible to understand how the care of pregnant women is with them, showing considerable deficiencies in their self-care, be it emotional, physical or mental, suggesting great reflections on the theme.